PENGARUH TINGKAT PENDIDIKAN ORANG TUA DALAM MENINGKATKAN MOTIVASI BELAJAR SEJARAH SISWA KELAS XI IPS DI MAN BINTAN - Khrisfison, Khrisfison; Yulia, Desma (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2023)
Education as an effort made by parents in guiding, directing their children in the desired teaching and learning process. Education, like learning, is a lifelong process that usually takes place in an unlimited shared environment and context. This study aims to describe the flow of parents to students' learning interests. This type of research is quantitative research with a correlation descriptive approach. The study begins by describing the present situation and what is assumed to be a result of factors having already reacted previously. The population in this study is all class XI students of MAN Bintan. The sampling technique uses a saturated sampling technique. The sample in this study was class XI social studies students. This type of research was carried out using a research population consisting of all class XI students of MAN Bintan. The result of this study is that the influence of parental education on student learning motivation, so this research can be used as a foundation for parents and teachers in motivating the learning of grade XI students of MAN Bintan. The hypothesis proposed which reads there is an influence of parental education on student learning motivation is proven to be (0.927. 0.361), thus the research that the author conducted and looked at the results of the study can be concluded that there is an influence of parental education on student learning motivation, then the alternative hypothesis (Ha) proposed is accepted. Keywords: history education; madrasah; Social Sciences